Establishment of the immunological self in juvenile Patiria pectinifera post-metamorphosis - Taguchi, Mizuki; Minakata, Kota; Tame, Akihiro; Furukawa, Ryohei (Frontiers in Immunology, 2022)
Ontogeny of the immune system is a fundamental immunology issue. One indicator of immune system maturation is the establishment of the immunological self, which describes the ability of the immune system to distinguish allogeneic individuals (allorecognition ability). However, the timing of immune system maturation during invertebrate ontogeny is poorly understood. In the sea star Patiria pectinifera, cells that have dissociated from the embryos and larvae are able to reconstruct larvae. This reconstruction phenomenon is possible because of a lack of allorecognition capability in the larval immune system, which facilitates the formation of an allogeneic chimera. In this study, we revealed that the adult immune cells of P. pectinifera (coelomocytes) have allorecognition ability. Based on a hypothesis that allorecognition ability is acquired before and after metamorphosis, we conducted detailed morphological observations and survival time analysis of metamorphosis-induced chimeric larvae. The results showed that all allogeneic chimeras died within approximately two weeks to one month of reaching the juvenile stage. In these chimeras, the majority of the epidermal cell layer was lost and the mesenchymal region expanded, but cell death appeared enhanced in the digestive tract. These results indicate that the immunological self of P. pectinifera is established post-metamorphosis during the juvenile stage. This is the first study to identify the timing of immune system maturation during echinodermal ontogenesis. As well as establishing P. pectinifera as an excellent model for studies on self- and non-self-recognition, this study enhances our understanding of the ontogeny of the immune system in invertebrates.